Some Methodological Issues Concerning Comparative Hospital-Organization Studies - Graeff, Claude L. (Academy of Management Review, 1980)
There are methodological issues associated with using hospital ownership and size as determinants of the structure and behaviors of hospitals. Theoretical and empirical inconsistencies reported in the literature prompted me to examine the relationships between ownership and size for a large sample of general hospitals (i.e., hospitals in one domain). The results of my investigation point to the advisability of including hospitals with religious affiliations in studies of this type. Some of the methodological issues pertinent to hospital-organization studies are relevant to other organization research.